The (Avoidable) Effects of Territorially Different Approaches to Trademark and Copyright Exhaustion - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2014)
In March 2013, the Supreme Court of the United States made copyright history when it issued its decision in Kirtsaeng v. Wiley & Sons and ruled that the principle of copyright exhaustion as provided in section 109(a) of the Copyright Act applies equally to products manufactured and lawfully distributed in the United States as well as in foreign countries. It took over two decades of litigation for the Court to reach this position and clarify that genuine (non-counterfeit) books, pictures, software, and other copyrighted products can be freely imported into the United States not solely by copyright owners but also by independent third parties ñ the so-called gray marketers ñ regardless of where the products were ìlawfully madeî and first sold in the global market. The impact of the decision in Kirtsaeng, however, goes beyond international trade in books, pictures, and other communicative products, which are traditionally the subject matter of copyright protection. It directly extends to international trade in many other consumer products such as shampoos, watches, and chocolate. Even though these products cannot be copyrighted in their entirety because they are non-copyrightable articles, they frequently carry ìincidental featuresî such as decorations, product design, product packaging, creative labels, logos, and so forth that can qualify for copyright protection. In recent years, copyright protection for these incidental product features has become increasingly popular in the business world.